Recurrent Ureteral Obstruction Revealing Malignant Lymphoma in a Young Adult : A Case Report - Faathira Amalika Dewinadira Yusna; Abdul Malik Yusuf (The International Journal of Medical Science and Health Research, 2026)
Introduction Extranodal presentations of malignant lymphoma represent a significant diagnostic challenge for clinicians, as they frequently mimic more common organ-specific pathologies. While the lymphatic system is the primary origin of these neoplasms, approximately 25% to 40% of Non-Hodgkin Lymphoma (NHL) cases originate in extranodal sites.1 Genitourinary (GU) tract involvement is particularly rare, accounting for less than 5% of all primary extranodal lymphomas.4 Among GU involvements, prostatic and ureteral infiltrations are exceedingly uncommon, often manifesting as non-specific lower urinary tract symptoms (LUTS) or acute renal failure due to obstructive uropathy.6 In young adults, the diagnosis of malignant ureteral obstruction (MUO) is often delayed because medical attention initially focuses on metabolic urolithiasis or congenital anatomical anomalies.9 Case Illustration A 27-year-old male presented with a history of a neck tumor excision in 2022, which initially suggested Hodgkin Lymphoma (HL) or a Giant Cell Soft Tissue Tumor. Due to the patient’s refusal of systemic chemotherapy, the disease progressed over three years. In June 2025, he presented with acute-on-chronic kidney injury (AKI/CKD) and bilateral hydronephrosis. Endoscopic evaluation through ureterorenoscopy (URS) revealed no lithiasis but identified significant bilateral ureteral stiffness and strictures. Despite temporary stabilization with double-J (DJ) stents, the patient experienced recurrent obstruction within two months. Subsequent transurethral resection of the prostate (TURP) and ureteral evaluation revealed widespread mural infiltration. Histopathology and immunohistochemistry (IHC) confirmed a malignant tumor suggestive of lymphoma, with leukocyte common antigen (LCA) and CD20 positivity. Further staging identified systemic lymphadenopathy, chylothorax, and sclerotic/lytic spinal metastases at the C1, C4, and TH3 levels. The patient eventually succumbed to complications of uremic encephalopathy and disseminated disease. Discussion The diagnostic hallmark of this case was the "stiff ureter" sign observed during endoscopy, indicating direct mural infiltration of neoplastic cells rather than simple extrinsic compression by lymph nodes.8 The clinical progression highlights the deceptive nature of prostatic lymphoma, which often presents with normal prostate-specific antigen (PSA) levels, thus evading traditional screening protocols.7 The case further explores the "gray zone" between Hodgkin Lymphoma and high-grade B-cell Non-Hodgkin Lymphoma, emphasizing the biological continuum and the potential for transformation in inadequately treated patients.16 The role of aggressive surgical biopsy and multidisciplinary management in young adults with idiopathic urological obstruction is critical to prevent the transition from a potentially curable local disease to terminal systemic dissemination.19 Conclusion Heightened clinical suspicion for lymphoma must be maintained in young adults presenting with recurrent, rigid ureteral obstruction of unknown etiology. Early tissue sampling via TURP or URS is mandatory to differentiate rare secondary lymphomas from primary urothelial carcinomas. Comprehensive management requires a synergy between urology, nephrology for renal replacement therapy, and hematology-oncology for tailored chemotherapy protocols.19